Effect of Inhibitors on the Corrosion of AISI-1018 Steel in Sea-Water Environment - Mohammed Misbahul, Amin; Khairel Rafezi, Ahmad (Research India Publications, 2008)
Link to publisher's homepage at http://www.ripublication.com/ijoms.htm